Liver transplantation in people living with HIV: An Italian nationwide survey focusing on hepatocellular carcinoma and oncologic recurrences - Visco-Comandini, Ubaldo; Burra, Patrizia; Giannelli, Valerio; Morelli, Maria Cristina; Marrone, Giuseppe; Ponziani, Francesca Romana; Guerrini, Gian Piero; Di Benedetto, Fabrizio; Guaraldi, Giovanni; Puoti, Massimo; Malattie Infettive, SC; De Carlis, Luciano; et al. (Digestive and liver disease, 2025)
Liver transplantation in people living with HIV is a well-established procedure. However, HIV infection has been suggested to be associated with higher post-transplant HCC recurrence rates and overall decreased survival, although this is based on limited real-life data. From September 2023, we conducted a survey in all Italian Liver Transplant Centers to investigate real-life data regarding numbers, listing indications, percentages of post-transplant HCC recurrence, and de novo malignancies in HIV-positive subjects. By the end of 2022, 365 subjects had received liver transplants across 13 Italian Transplant Centers. After 2009, HCC emerged as the primary indication for transplantation, accounting for 54.6 % of cases. Downstaging or bridging procedures were performed in 69.3 % of patients. Starting from 2018, the Metroticket 2.0 HCC listing criteria were utilized to prevent futile procedures. Estimated survival rates at 1, 3, and 5 years were 84.1 %, 72.9 %, and 64.4 %, respectively. During a median follow-up of 5.5 years, the HCC recurrence rate was 18.9 %, and post-transplant diagnosis of malignancies other than HCC (de novo tumors) was unexpectedly reported in 12.1 % of subjects. As reported by the survey, post-transplant HCC recurrences and survival rates at years 1 and 3 align with HIV-uninfected patients, while the 5-year survival rate is reduced.